Analysis of Knowledge Sharing Success in Multinational Firms: Organizational Culture Perspective - Supiyandi, Supiyandi; Hasanuddin, Muhammad; Rizki, Cindy Atika; Khodijah, Siti (Journal of Computer Science, Artificial Intelligence and Communications, 2025)
This study explores the critical role of organizational culture in shaping the success of knowledge-sharing initiatives within multinational firms. As knowledge becomes a key competitive asset in the global business environment, organizations increasingly rely on effective knowledge sharing to foster innovation, improve decision-making, and enhance operational efficiency. However, in multinational contexts, differences in national and organizational cultures can significantly influence the willingness and ability of employees to share knowledge. Using a qualitative approach, this research examines case studies of selected multinational corporations to identify cultural enablers and barriers to successful knowledge sharing. Key findings reveal that supportive leadership, trust-based relationships, open communication channels, and a shared vision contribute significantly to knowledge sharing success. Conversely, hierarchical structures, fear of judgment, and cultural misalignment across subsidiaries often hinder knowledge flows. The study highlights the importance of fostering a culture that values collaboration, openness, and mutual respect across diverse cultural settings. Practical implications include the need for multinational firms to design culturally sensitive knowledge management strategies and invest in leadership development that promotes inclusive and knowledge-friendly environments. The findings contribute to both academic and practical discussions by demonstrating that knowledge sharing is not solely a technical challenge but also a deeply cultural one, requiring attention to the complex social dynamics within global organizations.